Determine the optimal policy for the function of Pareto distribution reliability estimated using dynamic programming - صالح, سرمد علوان; خليل, سميرة (Journal of Economics and Administrative Sciences, 2011)
The goal (purpose) from using development technology that require mathematical procedure related with high Quality & sufficiency of solving complex problem called Dynamic Programming with in recursive method (forward & backward) through  finding series of associated decisions for reliability function of Pareto distribution estimator by using two approach Maximum likelihood & moment .to conclude optimal policy